INOVASI PELAYANAN KESEHATAN - Febri Yuliani, Nila Riwayati, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2020)
Health Service Innovation. This research is motivated by the importance of making a change in health services to the community by innovating health services. Innovation in the public sector is now a necessity to make the availability of services that are increasingly easy, inexpensive, affordable and equitable. The existence of innovation is very important for public services in order to provide the latest breakthroughs that can improve the quality of service. This study aims to analyze the innovation of health services provided to the community in the working area of Kampar Kiri Hulu II Health Center, Kampar Kiri Hulu II Subdistrict. This study uses a qualitative descriptive research method approach. Data collection techniques using questionnaires, interviews, and observations. Data analysis in this study uses interactive model analysis from Miles and Huberman which includes: data reduction stage, data presentation, and data verification to draw conclusions. The results of the study concluded that health services at the Kampar Kiri Hulu Public Health Center II desperately needed innovation in health services ranging from the number of officers, advice on service infrastructure, access that was difficult to reach, non-existent means of transportation, no network or access to information. This greatly requires changes and innovations in health services so that health services can reach people living in isolated areas such as the Kampar Kiri Hulu II area. While the factors that influence the innovation of health services are the relatively low number of officers, no means of transportation, and no access to communication. Whereas community support is good in accepting innovations in health services sought by health workers with all limitations.